Keanekaragaman Jenis Ikan di Sepanjang Sungai Boyong – Code Propinsi Daerah Istimewa Yogyakarta - Tri Trijoko; Donan Satria Yudha; Rury Eprilurahman; Setiawan Silva Pambudi (Journal of Tropical Biodiversity and Biotechnology, 2016)
The diversity of freshwater fishes which inhabit in the river of Daerah Istimewa Yogyakarta is not yet well documented. Complete documentation is needed as starting point and continuous research on the fish diversity in DIY. Boyong-Code River flows across the DIY, and it upstream is located on the hillside of Merapi volcano. The Code River upstream is called Boyong River. The research was aimed to acquire data about the diversity of fish fauna along the Boyong-Code River in the DIY. Further, the research purpose is to know which species are rare, potential for aquaculture, and introductive. Samples are taken along the Boyong-Code River starting from upstream to downstream. Samples were collected using Purposive Random Sampling methods with fishnets. Sampling area generally divided into three location i.e., upstream, middle-stream and downstream. Species diversity of fish in the Boyong-Code River is consisted of 24 species, with 5 introductive species. There are eleven native fish species which are potential for cultivation (aquaculture), i.e.: Barbodes binotatus, Mystacoleucus obtusirostris, Rasbora lateristriata, Rasbora argyrotaenia, Barbonymus balleroides, Osteochilus vittatus, Hampala macrolepidota, Anabas testudineus, Channa striata, Clarias leiacanthus and Clarias batrachus. The Boyong-Code River is a decent habitat for fishes. Many introduced fishes starting to invade the Boyong-Code River intentionally or unintentionally by human